Business Model Canvas Training for Entrepreneurial Mindset among MIPA Students - Helmy Syakh Alam; Linda Yupita (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The gap between strong technical science competencies and limited business literacy remains a key challenge for senior high school students, particularly those in Mathematics and Natural Sciences (MIPA) programs. Although MIPA students generally demonstrate strong analytical abilities, they often lack a structured framework to translate scientific ideas into viable business models. This community engagement program aimed to strengthen students’ entrepreneurial mindset and business planning competence through Business Model Canvas (BMC) training. The program was conducted at SMA Harapan Nusantara and involved 40 MIPA students using a participatory workshop method that combined conceptual delivery, case-based discussions, and direct group practice. Effectiveness was evaluated using a one-group pre-test and post-test design, with data analyzed through descriptive statistics and Normalized Gain (N-Gain). The results indicated a significant improvement in understanding, with the mean score increasing from 60.00 in the pre-test to 88.00 in the post-test. The N-Gain score of 0.70 falls within the high-effectiveness category, indicating that the BMC-based intervention was highly effective in improving students’ business planning competence. Beyond cognitive gains, the program also encouraged a shift in students’ perspectives from a product-oriented focus to more market- and value-oriented thinking. These findings suggest that integrating BMC training into co-curricular activities has strong potential as an effective strategy for fostering entrepreneurship among science-track students at the secondary education level.